Assessment of disaster risk management knowledge among households in the South Gondar Zone: The case of kebeles affected by disasters - Temesgen Alemu Tilahun; Abraham Mebrat Asmare; Tesfahun Asmamaw Kassie (Social Sciences and Humanities Open)
This study highlights the challenges in disaster risk management in Ethiopia, particularly due to inadequate household knowledge of essential concepts. Using a quantitative cross-sectional design, the research surveyed 412 households in the South Gondar Zone to assess their disaster awareness and the factors influencing it. Findings revealed that 77% of households had low knowledge levels, with rural areas especially those frequently affected by hazards showing significantly lower awareness than urban areas. Factors such as location, age, education, economic status, religion, and experience with Indigenous practices were found to influence knowledge. Significant statistical relationships were observed between knowledge levels and Woredas (χ2 = 6.5, p = 0.03), the nine kebeles (χ2 = 63.6, p = 0.001), and economic status of the households (χ2 = 21.6, p = 0.0003). The study concludes that low knowledge levels increase vulnerability to disasters, emphasizing the need for improved education on disaster risk management, especially in rural and affected areas. This study revealed higher level of disaster knowledge among illiterate and low economy class households, which provides a new insight towards the effort to enhance risk wisdom. Recommendations include integrating disaster management concepts into formal education, a focus on rural and disaster affected areas, and addressing existing knowledge gaps through targeted strategies.